Research progress of treatment of functional dyspepsia with traditional Chinese medicine compound based on cell signal pathway - Song, Yujiao; Yin, Defei; Zhang, Zhenyi; Chi, Lili (Frontiers in Pharmacology, 2023)
Functional dyspepsia (FD) is the most common clinical gastrointestinal disease, with complex and prolonged clinical symptoms. The prevalence of FD is increasing year by year, seriously affecting the quality of life of patients. The main causes of FD are related to abnormal gastrointestinal dynamics, increased visceral sensitivity, Helicobacter pylori (HP) infection, intestinal flora disturbance and psychological factors. A review of the relevant literature reveals that the mechanisms of traditional Chinese medicine(TCM) in the treatment of FD mainly involve the following pathways:5-HT signal pathway,AMPK signal pathway,C-kit signal pathway,CRF signal pathway,PERK signal pathway,NF-κB signal pathway. Based on a holistic concept, TCM promotes gastrointestinal motility, regulates visceral sensitivity and alleviates gastrointestinal inflammation through multiple signal pathways, reflecting the advantages of multi-level, multi-pathway and multi-targeted treatment of FD.